From cave to dolmen ritual and symbolic aspects in the prehistory between Sciacca, Sicily and the central Mediterranean - Gullì, Domenica 1961- (Archaeopress Archaeology, 2014)
"This book brings together the scientific contributions of a wide panel of Sicilian and mainland Italian specialists in prehistory. Taking inspiration from a conference organised by the Soprintendenza ai Beni Culturali e Ambientali of Agrigento and by the municipal council of Sciacca in November 2011, the decision was taken to broaden and deepen some of the main themes discussed on that occasion. Therefore this book focuses on the Sciacca region and its landscape which is extraordinarily rich in natural geological phenomena and associated archaeological activity, for example the Grotta del Kronio and the numerous dolmens present nearby. This volume seeks to explore the various aspects - habitational or ritual - of the prehistoric use of the numerous caves present in the region and to analyse the many features of the island's megalithic architecture. The text includes an historical review of the processes of discovery of the archaeological evidence, also an account of the current research projects and research activities." -- Publisher
Includes bibliographical references
Keywords: Funde; Höhle; Dolmen; Sciacca; Sizilien; Antiquities, Prehistoric / Italy / Sicily; Cave dwellers / Italy / Sicily; Prehistoric peoples / Italy / Sicily; Antiquities; Konferenzschrift -- 2011 -- Sciacca; Aufsatzsammlung